Financial Markets and the Behavior of Private Savings in Latin America - Liliana Rojas-Suárez; Steven R. Weisbrod (Inter-American Development Bank, Office of the Chief Economist, 1997)
This paper complements previous studies by arguing that the low private savings ratio in Latin America can be associated with the limited confidence of households and businesses in domestic financial institutions. Previous studies have established a relationship between private savings and financial markets either by using a measure of `financial depth` or a measure of `borrowing constraints. ` This paper offers an alternative view by claiming that the private savings rate relates positively to the confidence of the private sector in the strength of the financial system and that the latter concept can be approximated by the ratio of corporate demand for bank liquid assets. Latin American countries have lower private savings rates than other developing and most industrial countries. They also display the highest corporate to household bank deposit ratios among the three groups of countries considered here. Further, the ratio of corporate to household deposit holdings is strongly correlated with other indicators of banking system fragility.
Keywords: 330